Strengthening the Competency of Student Development Personnel in Higher Education Institutes - Chumphon, Prasat; Meekun, Kosol; Poovatanakul, Vipaporn; Rasanond, Tharin (Journal of Buddhist Education and Research (JBER), 2024)
This article aims to present educational guidelines for developing student development personnel in higher education institutions, with an emphasis on enhancing key competencies. Competency is a characteristic of an individual that directly impacts work performance. To develop personnel with the necessary competencies-knowledge, skills, and attitudes—student development must align with the goal of fostering desirable graduate characteristics for the 21st century. The development of personnel competencies in student development departments within higher education institutions requires appropriate knowledge and methods. This involves understanding causal factors and applying a development model based on systematic and rational study. Such a model fosters work behavior that effectively achieves organizational goals. These guidelines are intended to support the development of competencies among student development personnel, enabling them to effectively prepare students for success in the 21st century